Prediction of ceramic foams permeability using Ergun's equation - Murilo D.M. Innocentini; Vânia R. Salvini; Alvaro Macedo; Victor C. Pandolfelli (Materials Research, 1999)
SiC-Al2O3 ceramic foams with 30 to 75 pores per linear inch (ppi) were used to access the application of pore size obtained by image analysis to estimate the cellular materials permeability through Ergun's equation. Samples were sliced and the pore size distribution, cross-sectional porosity and pore density were evaluated as a function of the slice thickness based on optical and X-ray computerized tomography acquired images. The average pore sizes were used to calculate permeability constants (k1 and k2) of Ergun's equation, which were compared to those experimentally obtained under water flow. Results indicated that the optical diameter distribution was very sensitive to the number of pore layers. Deviation between experimental and calculated values depended on the slice thickness. Nevertheless, the introduction of pore size obtained by image analysis into Ergun's equations seems to give fair results to assess the permeability of ceramic foams.